Critical aspects of alloying and stress relaxation in ge/si(100) islands - Hadjisavvas, George C.; Kelires, Pantelis C. (My University, 2005)
We report Monte Carlo simulations of alloying and stress relaxation in Ge/Si(100) dome and pyramidal islands. In both cases, the simulated composition profiles consist of inhomogeneous Si-rich cores and outer Ge-rich shells. Comparison to experimentally deduced profiles gives us the opportunity to discuss some of the most controversial aspects of the problem. We propose that, in addition to surface events and kinetically driven alloying, volume diffusion and stress-driven intermixing need to be considered for a global interpretation of experimental results.
Keywords: Islands; Alloys